Impact of Gender Inequality in Education and Labour Force Participation on Economic Growth in Nigeria - Adeleke, Omolola Rebecca; Duru, M. C.; Yakubu, Alfa; Ikubor, Jude O. (Social Science Research, 2024)
This study investigated the impact of gender inequality in education and labour force participation on economic growth in Nigeria from 1991 to 2022 using the Autoregressive Distributed Lag (ARDL) model. Data on gross domestic product growth rate (GDPG) which is the dependent variable, gender parity index used to proxy gender inequality in education (GIE), ratio of female-to-male labour force participation used to proxy gender inequality in labour force participation (GLFP), population growth rate (POPG), dependency ratio (DRwp) were sourced from World Bank Development Indicators (2024) and data on capital formation (KF)was sourced from Central Bank Statistical Bulletin (2023). The estimated ARDL model indicated that gender inequality in education proxied had a negative significant impact on economic growth in the long run and a positive significant relationship with economic growth in the short run. On the other hand, gender disparity in labour force participation had no consequences on economic growth in the short and long run. Based on the findings the study recommends that more attention should be given to reducing the disproportionate female-to-male educational enrolment at all levels in Nigeria. Policies and programmes that promote equal access to rights, opportunities and privileges for males and females should be encouraged, thus, reducing gender inequality in all forms so that the nation can achieve economic growth that is inclusive and sustainable in the long run.